Can an El Niño induced drought hamper the reforestation of the subtropical forest? - (:unkn) unknown (My University, 2021)
The selection of reforestation species that promote rapid forest establishment has now become more challenging as a result of global climate change. This is because a recent increase in droughts associated with the El Niño Southern Oscillation is presenting a critical challenge to forest seedling survival and growth, thus threatening biodiversity and ecosystem services supply. The severe drought associated with the 2014–2016 El Niño Southern Oscillation event presented an opportunity to assess its impact on the reforestation success of a subtropical forest in Durban, South Africa. We assess how microtopographic positions (specifically, dry and moist microhabitats) influenced seedling/sapling survival and growth performance (stem diameter and height, and canopy width) of four dominant planted tree species (Bridelia micrantha, Erythrina lysistemon, Millettia grandis, and Vachellia natalitia) under a severe drought, measured a month after transplanting and 13 months post-transplanting, after the drought began. Survival ranged from 73% to 93%, but seedlings/saplings in the moist microhabitat had higher survival rates and higher growth rates than species in the dry microhabitat. A higher survival rate exhibited by M. grandis followed by V. natalitia and E. lysistemon in both the dry and moist microhabitats suggests these three species are good pioneers for reforestation in areas that are predicted to experience frequent and intense droughts. Results from this study highlight the importance of considering microtopographic positions, as well as understanding species-specific habitat requirements when selecting reforestation species under the current and future climatic conditions.
Keywords: African Research